Biology of Tetrastichus brontispae (Ferriere) (Hymenoptera: Eulophidae), the Coconut Leaf Beetle Parasitoid - Zahlul Ikhsan; Hidrayani Hidrayani; Yaherwandi Yaherwandi; Aulia Oktavia (Green Engineering Society, 2023)
Biological control using parasitoids should be carried out to reduce the population of Brontispa longissima without pesticides. Tetrastichus brontispae is a larva-pupa parasitoid and is a gregarious parasitoid. Many factors can influence the biology of the parasitoid, which consists of biotic and abiotic factors. The existence of a host is one of the biotic factors that influence the life of parasitoids. The aim of the study was to study various biological parameters of the T. brontispae parasitoid which included the shape, size, color and length of each egg, larva, pupa, and imago stages as well as personality, sex ratio and number of hosts parasitized by female T. brontispae imago. The research was carried out in the form of an experiment using a completely randomized design. Experiments for biological observations of female T. brontispae parasitoids consisted of 4 treatments and 10 replications. The period of development, offspring, and sex ratio of the parasitoid Tetrastichus brontispae were studied using young pupa Brontispa longissima as hosts. Maintenance is carried out by inserting the parasitized larvae or pupa into the test tube provided. T. brontispae is a gregarious endoparasitoid. The development period from egg to imago is 18.95 ± 0.75 days. The length of life of the imago was significantly different between females (9.7 ± 0.51 days) and males (4.5 ± 0.52 days)—honey in increasing lifespan and enhancing T. brontispae offspring. The offspring of a female is 17.50 ± 1.08, with a female proportion of 60.12%. Imago T. brontispae fed honey had a longer and higher actual life span than without honey. Apart from the honey feed, the presence of a host can also affect T. brontispae.